Factors related to advanced colorectal neoplasm at the Policlínico Peruano Japonés - V. Parra-Pérez; J. Watanabe-Yamamoto; A. Nago-Nago; M. Astete-Benavides; C. Rodríguez-Ulloa; G. Valladares-Álvarez; N. Núñez-Calixto; M. Yoza-Yoshidaira; T. Gargurevich-Sánchez; J. Pinto-Sánchez; J. Niebuhr-Kakiuchi; G. Uehara-Miyagusuku; et al. (Revista de Gastroenterología de México (English Edition), 2015)
Background: Identifying persons at high risk for advanced colorectal neoplasia can aid in the prevention of colon cancer. Previous studies have shown that some patients can present with proximal advanced neoplasia with no distal findings. Aims: To determine the factors related to advanced neoplasia and advanced proximal colorectal neoplasia in a Latin American population. Material and methods: A prospective, cross-sectional, observational, analytic study was conducted. It included patients that underwent colonoscopy at the Policlínico Peruano Japonés within the time frame of January and July 2012. Advanced neoplasia was defined as the presence of lesions ≥ 10 mm with a villous component, high-grade dysplasia, or carcinoma. The splenic flexure was the limit between the proximal and distal colon. Results: A total of 846 patients were included in the study. Advanced neoplasia was detected in 108 patients (12.8%) and advanced proximal neoplasia in 55 patients (6.7%), 42 (76.4%) of whom had no neoplasia in the distal colon. Factors related to advanced neoplasia found in the multivariate analysis were age, at the intervals of 50-59 (p = 0.019), 60-69 (p = 0.016), and ≥ 70 years (0.002) and male sex (p = 0.003). In the evaluation of advanced proximal neoplasia, the multivariate analysis identified the 60-69 year age interval (p = 0.039) and advanced distal neoplasia (p = 0.028) as factors related to advanced proximal disease. The ROC curve established the age cut-off point at 60 years for initially performing colonoscopy, rather than sigmoidoscopy. Conclusions: Age and sex are related to advanced neoplasia, whereas age and advanced distal neoplasia are related to advanced proximal neoplasia.